(untitled) (Orangeburg, SC, 1999)
This is a color field guide with 267 color photos of insects and their natural enemies (predators, parasites and insect pathogens) associated with vegetables and soybean in Southeast Asia.
Keywords: Vegetables,soybean,Insect pests; Diseases and pests,Biological control,diseases and pests,Biological control; Southeast Asia,Southeast Asia